2007
DOI: 10.1002/nau.20421
|View full text |Cite|
|
Sign up to set email alerts
|

Pudendal entrapment as an etiology of chronic perineal pain: Diagnosis and treatment

Abstract: Pudendal entrapment can be a cause of chronic, disabling perineal pain in both men and women. Since symptomatic patients seek medical care from many different medical specialists, a reliable diagnostic protocol should be established. For patients refractory to conventional interventions, surgical decompression of the pudendal nerve can improve pain-related symptoms and disability. With ongoing work on this subject, which is a difficult disorder to accurately diagnose and treat, a better awareness of pudendal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
1
9

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 17 publications
1
60
1
9
Order By: Relevance
“…Although there is no single neurodynamic test for this nerve, symptoms may be elicited with passive internal and external rotation of the hip and resisted hip abduction and adduction at 90 degrees of hip extension. 60 …”
Section: Femoroacetabular Joint Derangement (Ie Osteoarthritismentioning
confidence: 99%
“…Although there is no single neurodynamic test for this nerve, symptoms may be elicited with passive internal and external rotation of the hip and resisted hip abduction and adduction at 90 degrees of hip extension. 60 …”
Section: Femoroacetabular Joint Derangement (Ie Osteoarthritismentioning
confidence: 99%
“…Popeney et al [49] chose decompression surgery, demonstrating good results in 50 patients. Robert et al [50] showed the better results with surgical vs. medical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…b Nach Implantation der 5-6-5-Plattenelektrode in die Höhe BWK12/LWK1 beschrieb die Patientin ein positives Stimulationsergebnis, das nach positiver Austestung über einen externen Pulsgeber die Indikation zur Implantation des Neurostimulators rechtfertigte. c Die anteroposteriore Röntgenaufnahme zeigt die Plattenelektrode in Höhe des Conus medullaris bei BWK12/LWK1 keine sensiblen Ausfallserscheinungen und eine Schmerzlinderung nach Pudendusblockade gehören zu diesen Kriterien [5,8,14]. Die Computertomographie-gestützte Infiltration des N. pudendus im Alcock-Kanal kann konstante Verbesserungen der Lebensqualität bewirken [2,14].…”
Section: Therapie Und Verlaufunclassified
“…Allerdings ist mit nur 20% die Zunahme der Lebensqualität anhand des "Quality of Life (QOL) index" ein eher geringer Effekt, der bei schwerwiegenden Fällen kaum zu einer spürbaren Besserung führt [6]. Auch die chirurgische Dekompression kann in bis zu 60% der Patienten eine unterschiedlich ausgeprägte Schmerzlinderung bewirken [8,9,11]. Aber diese therapeutischen Maßnahmen sind bei intraoperativen Schädigungen eines nicht eingeengten N. pudendus mit nachfolgender Pudendusneuralgie verständlicherwei-se nicht wirksam, sodass sich diese iatrogene Form der Neuralgie den herkömm-lichen Therapiestrategien entzieht.…”
Section: Therapie Und Verlaufunclassified